Studying relationship between increased 5-methylcytosine oxidation and expression of cancer stem cell markers in glioblastoma cell lines - Wijeyagumar, Vithusha (2018)
DNA methylation (5-methylcytosine, 5mC) is an epigenetic modification generated by the addition of a methyl group to the 5 position on the cytosine ring of the DNA and it is important for a range of biological processes such as development and chromosome stability. 5mC can be enzymatically oxidised to 5-hydroxymethylcytosine, 5-fCformylcytosine and 5-carboxylcytosine (5caC) by TET proteins. These oxidised forms of 5mC may both serve as intermediates in the process of active DNA demethylation and/or contribute to the regulation of transcription. According to our results, 5caC exhibits heterogeneous distribution between different cells in glioblastomas (GBM), aggressive gliomas classified as grade IV astrocytoma which is always rapidly growing and highly malignant. Interestingly, GBMs are highly heterogeneous cancers containing a cancer stem cell (CSCs) subpopulation which is responsible for the reoccurrence of the tumour after treatment.